2020
DOI: 10.1038/s41467-020-18979-4
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 activation in lung mesenchyme drives sex- and age-dependent pulmonary structure and function decline

Abstract: Lymphangioleiomyomatosis (LAM) is a rare fatal cystic lung disease due to bi-allelic inactivating mutations in tuberous sclerosis complex (TSC1/TSC2) genes coding for suppressors of the mechanistic target of rapamycin complex 1 (mTORC1). The origin of LAM cells is still unknown. Here, we profile a LAM lung compared to an age- and sex-matched healthy control lung as a hypothesis-generating approach to identify cell subtypes that are specific to LAM. Our single-cell RNA sequencing (scRNA-seq) analysis reveals no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…However, this was unable to be investigated in vivo since LAM lung cells have not been able to be grown in mice [ 7 , 8 ]. Wnt pathway genes were also observed in LAM-specific mesenchymal lung cells by two important single-cell RNA sequencing (scRNAseq) studies in LAM [ 44 , 45 ].…”
Section: Mtor and Wnt Pathway Crosstalkmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this was unable to be investigated in vivo since LAM lung cells have not been able to be grown in mice [ 7 , 8 ]. Wnt pathway genes were also observed in LAM-specific mesenchymal lung cells by two important single-cell RNA sequencing (scRNAseq) studies in LAM [ 44 , 45 ].…”
Section: Mtor and Wnt Pathway Crosstalkmentioning
confidence: 99%
“…Our research showed upregulation of the Wnt pathway in LAM-lung-specific mesenchymal cells [ 45 ]. To follow this up in vivo, we deleted the Tsc2 gene, specifically in mouse lung mesenchymal progenitor cells, resulting in progressive age-dependent enlargement of alveolar spaces, as well as pulmonary lung function decline [ 45 ].…”
Section: Mtor and Wnt Pathway Crosstalkmentioning
confidence: 99%
See 3 more Smart Citations